2020
DOI: 10.1021/acsbiomaterials.0c00844
|View full text |Cite
|
Sign up to set email alerts
|

Acute Implantation of Aligned Hydrogel Tubes Supports Delayed Spinal Progenitor Implantation

Abstract: An important role of neural stem cell transplantation is repopulating neural and glial cells that actively promote repair following spinal cord injury (SCI). However, stem cell survival after transplantation is severely hampered by the inflammatory environment that arises after SCI. Biomaterials have a demonstrated history of managing post-SCI inflammation and can serve as a vehicle for stem cell delivery. In this study, we utilize macroporous polyethylene glycol (PEG) tubes, which were previously found to mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 89 publications
1
18
0
Order By: Relevance
“…Once implanted, the tubes create a more pro-regenerative environment, serving as a privileged injection site for E14 spinal progenitors 2 weeks after injury. Our previous work showed that transplanted cell survival is enhanced when injected into the tubes, compared with direct transplantation into the injury, demonstrating the feasibility of using this as a cell-biomaterial system for SCI (Ciciriello et al, 2020). While survival did improve with the integrated tubes, the stem cell-influenced results of that study were minimized as functional and histological assessments occurred only 2 weeks after cell transplantation (4 weeks after injury).…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Once implanted, the tubes create a more pro-regenerative environment, serving as a privileged injection site for E14 spinal progenitors 2 weeks after injury. Our previous work showed that transplanted cell survival is enhanced when injected into the tubes, compared with direct transplantation into the injury, demonstrating the feasibility of using this as a cell-biomaterial system for SCI (Ciciriello et al, 2020). While survival did improve with the integrated tubes, the stem cell-influenced results of that study were minimized as functional and histological assessments occurred only 2 weeks after cell transplantation (4 weeks after injury).…”
Section: Discussionmentioning
confidence: 92%
“…In this study, we expand the passive microenvironment modulation of our macroporous PEG tubes to actively modify the transplantation microenvironment through lentiviral-mediated delivery of IL-10. Previously, we demonstrated the short-term feasibility of temporally flexible transplantation of enhanced green fluorescent protein (EGFP + ) embryonic Day 14 (E14) spinal progenitors into integrated PEG tubes (Ciciriello et al, 2020). Expanding on this prior work, in our current study we will implant IL-10 encoding lentivirus-laden tubes into a cervical (C5) lateral hemisection, and 2 weeks later inject EGFP + E14 spinal progenitors directly into the tubes at the lesion epicenter.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations